2003
DOI: 10.1053/jhep.2003.50019
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous viral clearance in patients with acute hepatitis C can be predicted by repeated measurements of serum viral load

Abstract: Early interferon (IFN) therapy prevents viral persistence in acute hepatitis C, but in view of the resulting costs and morbidity patients who really need therapy have to be identified. Twelve consecutive patients with acute hepatitis C (9 women, 3 men, mean age: 39.5 ؎ 18.8 y, genotype 1: 7, genotype 3a: 3, 2 could not be genotyped) were studied. The sources of infection were medical procedures in 6, sexual transmission in 3, and intravenous drug abuse in 3 patients. N atural history of acute hepatitis C virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
153
4
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(175 citation statements)
references
References 37 publications
(53 reference statements)
12
153
4
6
Order By: Relevance
“…Untreated, acute HCV infection progresses to chronic infection in 50-80% of patients (3)(4)(5) while the remainder appear to be able to clear the virus on their own. Several studies have suggested that female sex, symptomatic disease and high peak bilirubin levels are the strongest predictors of spontaneous viral clearance (6).…”
Section: Introductionmentioning
confidence: 99%
“…Untreated, acute HCV infection progresses to chronic infection in 50-80% of patients (3)(4)(5) while the remainder appear to be able to clear the virus on their own. Several studies have suggested that female sex, symptomatic disease and high peak bilirubin levels are the strongest predictors of spontaneous viral clearance (6).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis develops in 33-84% of patients with acute hepatitis C. [1][2][3][4] Once, chronicity has established, about one-third of patients develop liver cirrhosis within 15-25 years 5,6 with an annual risk of hepatocellular carcinoma in 1-4% in cirrhotic livers. [7][8][9] Several factors such as alcohol abuse, coinfection with HBV or HIV, gender or age at infection determine the highly variable course of liver disease in hepatitis C virus (HCV) infection.…”
Section: Introductionmentioning
confidence: 99%
“…Although serial assessment of IgM anti-HCV titres may help, 10 this test is not readily available, and only evaluation of the viral kinetics in the first weeks after presentation is really predictive of spontaneous clearance. 11 Since 2001, when a cohort study by Jaeckel et al 12 demonstrated that 6 months of treatment with standard IFN alfa 2b at doses comparable to those used for chronic hepatitis was enough to eradicate HCV infection in 98% of patients with acute hepatitis C, the issue of optimal treatment of AVH due to HCV has been a matter of hot debate. Albeit a fair number of studies (reviewed by metaanalysis in 13 ) show a net benefit of IFN therapy over no treatment in terms of duration of viraemia, rate of chronicity, and duration of biochemical alterations, there is still no consensus on whom to treat and the timing of treatment.…”
mentioning
confidence: 99%